Improving Municipal Management for Cities to Succeed - World Bank (Washington, DC, 2012)
Cities now host half the world's population and provide 70 percent of world Gross Domestic Product (GDP). Managing them well is vital for development. The Bank has assisted nearly 3,000 municipalities worldwide over the past decade. This Bank assistance has helped strengthen the planning, finance and service provision dimensions of municipal management through 190 operations identified by Independent Evaluation Group (IEG) as municipal development projects (MDPs). Best results for municipalities came through stronger flows of revenues, better financial management, information systems and ability to manage procurement. Weaker results were found in monitoring and evaluation, operations and maintenance, private finance of services and lack of poverty focus. The purpose of this IEG special study is to illuminate the scale and scope of Bank support for municipal development and to draw specific lessons from the achievements and failures of a sample of individual projects. The study focuses on three dimensions of municipal management; planning, finance, and service provision. The planning dimension refers to the capacity of a municipality to forecast and oversee its own progress. It includes information systems, monitoring and evaluation (M&E), city planning, and investment strategies. The finance dimension refers to how a municipality manages the resources needed to provide services to its constituents. It covers financial management, own-resource mobilization, access to credit, and private funding. The service provision dimension refers to the capacity of a municipality to manage the services required by city residents and business people through the effective prioritization of investments, management of competitive procurement, and sustaining of services through operations and maintenance (O&M).